PENGGUNAAN PENDEKATAN CTL UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI BAHASAN SEGI EMPAT DAN SEGITIGA - Ardiansyah Ardiansyah; Ahmad Zakaria (SIGMA, 2020)
The objective to be achieved in this study is to determine the activity, response and improvement of student learning outcomes in class VII One Roofing 1 Camplong Middle School on rectangular and triangular material. This research is a Classroom Action Research (CAR) and is carried out over two cycles with each through several stages, namely planing, action, observation / evaluation, and reflection. Researchers use the method of observation to determine student activity, a questionnaire to determine student responses, and tests to determine student learning outcomes. From the results of data analysis, it can be concluded that student activity has increased by 0.4, namely in cycle I amounted to 3.2 and in cycle II amounted to 3.6 while student responses were positive by obtaining an average in cycle I of 77% and in the second cycle by 79%. Then based on test results on average - an individual has increased by 5 where in the first cycle amounted to 70 and in the second cycle amounted to 75. While in classical also an increase, where in the first cycle reached 49% and in the second cycle reached 86.48%. So, student learning outcomes classically from cycle I to cycle II increased by 37.48%.